ONLINE LEARNING MEDIA IN HIGHER EDUCATION IN THE NEW NORMAL ERA - Nurhanna Harahap; Muhammad Rusli (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
This study aims to determine and describe (1) online learning media used in the teaching and learning process in the new normal era, (2) students’ understanding of the use of online learning media, (3) students’ preference of the way of communication, and (4) students’ preference of material form. The participants of this research are the students of English Education Study Program at Universitas Al Washliyah (UNIVA) Labuhanbatu. The instrument of the research is questionnaire distributed via Google Form. Data analysis technique used in this study consists of data colletion, data reduction, data display, and drawing conclusion. The result shows that the most frequently used online learning media are WhatsApp and Google Classroom. Almost all students understand how to operate WhatsApp, Zoom, and Email. As many as 47% students choose two-way semi communication in teaching learning process. Using video as the material form in teaching learning proces is the most preferred by students.